2005
DOI: 10.1128/jb.187.22.7753-7764.2005
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and Function of a Spore Coat-Associated Transglutaminase of Bacillus subtilis

Abstract: The assembly of a multiprotein coat around the Bacillus subtilis spore confers resistance to lytic enzymes and noxious chemicals and ensures normal germination. Part of the coat is cross-linked and resistant to solubilization. The coat contains -(␥-glutamyl)lysyl cross-links, and the expression of the gene (tgl) for a sporeassociated transglutaminase was shown before to be required for the cross-linking of coat protein GerQ. Here, we have investigated the assembly and function of Tgl. We found that Tgl associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 39 publications
6
64
0
Order By: Relevance
“…However, to date, Tgl-dependent cross-linking has been shown only for GerQ, making it the only known Tgl substrate in B. subtilis (19,25). Recent work has also provided additional evidence for Tgl-dependent cross-linking of GerQ, although the number of Tgl-dependent cross-linked species present in spore extracts in this recent study was greatly reduced compared to that in our wild-type spores (13,19).…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…However, to date, Tgl-dependent cross-linking has been shown only for GerQ, making it the only known Tgl substrate in B. subtilis (19,25). Recent work has also provided additional evidence for Tgl-dependent cross-linking of GerQ, although the number of Tgl-dependent cross-linked species present in spore extracts in this recent study was greatly reduced compared to that in our wild-type spores (13,19).…”
Section: Discussionmentioning
confidence: 41%
“…A number of coat proteins have been suggested to be involved in Tgl-mediated cross-linking (8,19,(24)(25)(26). However, to date, Tgl-dependent cross-linking has been shown only for GerQ, making it the only known Tgl substrate in B. subtilis (19,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iranzo et al (2002) suggested that transglutaminase may be involved in the formation of covalent cross-links between proteins during cell wall construction of Saccharomyces cerevisiae. In addition, some studies have shown that TGases are involved in the assembly of spore coat proteins of the genus Bacillus through epsilon-(gammaglutamyl)lysine bonds (KobAyAsHi et al, 1998;ZiLHão et al, 2005;PLáCIDo et al, 2008).…”
Section: Microbial Transglutaminasementioning
confidence: 99%
“…5,6) In prokaryotes, calcium-independent TGs with only one subunit have been discovered in Streptomyces 7,8) and Bacillus. 9,10) A typical microbial transglutaminase (MTG) was produced by the wild-type Streptomyces mobaraensis strain, which is widely used as a protein crosslinking enzyme, especially in food processing. 11) To date, the main source of MTG is conventional fermentation at high cost.…”
mentioning
confidence: 99%